A RISK STRATIFICATION SYSTEM TO DISCRIMINATE CONGESTIVE HEART FAILURE PATIENTS USING MULTI-VALUED COARSE-GRAINING LEMPEL-ZIV COMPLEXITY - CHANDRAKAR KAMATH (Journal of Engineering Science and Technology, 2015)
A risk stratification system to discriminate congestive heart failure (CHF) subjects from healthy subjects is proposed. All the previous research to detect CHF patients using Lempel-Ziv complexity measure had used binary coarse-graining (BLZC). In this work, we show that employing multi-valued coarse-graining Lempel-Ziv complexity (MLZC) improves the performance of classification. This finding is confirmed using receiver operating characteristic (ROC) plots. Compared to BLZC, MLZC with six partitions showed higher diagnostic parameters. The risk stratification system proposed in this paper will be a valuable asset to the clinician in the separation of CHF patients from the healthy group.